Implikasi Hukum Atas Kedudukan Warga Negara Asing Sebagai Ahli Waris Untuk Hak Milik Atas Tanah - Lynda Chayadi (Jurnal Ilmiah Penegakan Hukum, 2020)
The Property Rights in Article 20 paragraph (1) of the Basic Agrarian Law No. 5 Year 1960 (UUPA) is a hereditary, strongest, and most fulfilled right that a person can have on land. In Indonesia, only Indonesian Citizens with no dual citizenship can have the right to own land. The research method used is a normative juridical research that is prescriptive in which this research seeks to provide an overview or formulate a problem in accordance with the circumstances or facts that are associated with existing benchmarks / norms. From the results of the study it can be concluded that foreigners in principle are allowed to obtain ownership rights over the land through inheritance provided they continue to carry out their obligations in accordance with Article 21 paragraph (3) of the UUPA. This is because in the case of the action required by the foreigners, the Land Deed Making Officer (PPAT) and the National Land Agency (BPN) as authorized officials apparently still have differences of opinion regarding whether or not a foreigners’ heir may sign a Deed of Purchase (AJB), which is signed for the transfer of ownership rights to the land acquired. This theory is meant to support the people following the orders of Article 21, with the efforts of the foreigners’ being done well and thus minimising the problems that they might face